Thermodynamic parameters of an ultrasound relaxation process in 2-Nitrobutanol-1 - JUSZKIEWICZ, Adam; BARTYNOWSKA-MEUS, Zofia (Archives of Acoustics, 1980)
Measurements of the velocity and absorption coefficient of ultrasound were carried out in 2-nitrobutanol-1 with respect to the frequency of the sound and the temperature. The relaxation process can be accounted for in terms of a rotation about the C–C bond. The relaxation parameters for the observed process have been determined.